2013
DOI: 10.5888/pcd10.120214
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Price Reduction on Salad Bar Purchases at a Corporate Cafeteria

Abstract: The objective of this study was to determine the effect of a price reduction on salad bar purchases in a corporate cafeteria. We reduced the price of salad bar purchases by 50% during March 2012 and analyzed sales data by month for February through June 2012. We also conducted an anonymous survey. Salad bar sales by weight more than tripled during the price reduction and returned to baseline afterward. Survey respondents reported that the high price of salad relative to other choices is a barrier to purchases.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Pooling all studies, each 10% decrease in price increased consumption of healthful foods by 12% (95%CI: 10% to 15%) ( Fig 2A ). Fruits and vegetables were the most common target, including studies among adults in the US,[ 36 , 40 , 44 ] New Zealand,[ 27 ] South Africa,[ 23 ] and The Netherlands[ 51 ]; and among children in the US [ 34 ]. Most individual studies found significant effects; and pooling all studies, each 10% price decrease increased consumption of fruits and vegetables by 14% (95%CI: 11% to 17%).…”
Section: Resultsmentioning
confidence: 99%
“…Pooling all studies, each 10% decrease in price increased consumption of healthful foods by 12% (95%CI: 10% to 15%) ( Fig 2A ). Fruits and vegetables were the most common target, including studies among adults in the US,[ 36 , 40 , 44 ] New Zealand,[ 27 ] South Africa,[ 23 ] and The Netherlands[ 51 ]; and among children in the US [ 34 ]. Most individual studies found significant effects; and pooling all studies, each 10% price decrease increased consumption of fruits and vegetables by 14% (95%CI: 11% to 17%).…”
Section: Resultsmentioning
confidence: 99%
“…The context for studies varied greatly, with 15 Organization for Economic Co‐operation and Development (OECD) countries represented. The majority of studies were conducted in the United States (n = 56) or Canada (n = 13) . Studies encompassed food service (n = 44), grocery (n = 56), and mixed (n = 7) retail settings including cafeterias (n = 24), full service restaurants (n = 18), corner stores and/or grocery stores (n = 19), supermarkets (n = 16), vending machines (n = 13), quick‐service restaurants (n = 13), and cafés (n = 5)…”
Section: Resultsmentioning
confidence: 99%
“…16-18 For example, Kottke and colleagues discovered that reducing salad bar prices in a worksite cafeteria by 50% resulted in three times more salad bar sales during the intervention period, with sales returning to normal after the intervention. Further, participants from this study indicated that the high price of salad is a barrier to selection.…”
Section: Discussionmentioning
confidence: 99%
“…Further, participants from this study indicated that the high price of salad is a barrier to selection. 18 Other studies suggest that price reduction of healthy foods does not negatively impact profits. 16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation